HUBUNGAN PARITAS DENGAN KEJADIAN PLASENTA PREVIA - Lia Fitria (Oksitosin : Jurnal Ilmiah Kebidanan, 2014)
Placenta previa is a placenta that is abnormally located in the lower uterine segment until covers part or all of the uteri internum which causing serious mortality for both fetus and mother. Maternal death is caused by vaginal bleeding, the incidence of placenta previa often more three times in multiparous than primiparous women. Placenta previa is caused by reduced vascularization and atrophic changes in the decidua past due deliveries in multiparous. The incidence of placenta previa greater because endometrial less fertile state at high parity. This study aims to the determine the relationship of parity with the incidence of placenta previa in dr. Abdoer Rahem Situbondo Hospital year 2013-2014.The type of this research is an analytic study. The Sample is 39 respondents. out 1475 deliveries , the sampling technique is a total sampling. This research uses the Chi-Square test with α = 0.05 level. Conclusions from this research is that there is a significant correlation (p = 0.05), namely (0.000 <0.05) between parity with the incidence of placenta previa. Keywords : Paritas, Plasenta Previa ABSTRAK Plasenta previa adalah plasenta yang letaknya abnormal yaitu pada segmen bawah rahim sehingga menutupi sebagian atau seluruh ostium uteri internum yang menyebabkan kematian yang serius baik bagi janin dan ibu. Kematian pada ibu disebabkan oleh perdarahan vagina. Kejadian plasenta previa tiga kali lebih sering pada wanita multipara daripada primipara. Plasenta previa disebabkan vaskularisasi yang berkurang dan perubahan atrofi pada desidua akibat persalinan masa lampau pada multipara. Kejadian plasenta previa makin besar karena keadaan endomentrium kurang subur pada paritas tinggi. Penelitian ini bertujuan mengetahui adanya hubungan paritas dengan kejadian plasenta previa di RSUD dr. Abdoer Rahem Situbondo Tahun 2013-2014. Jenis penelitian ini yaitu penelitian analitik. Sampel sebanyak 39 responden yang mengalami plasenta previa dari 1475 persalinan. Teknik sampling adalah Total sampling. Penelitian ini menggunakan uji Chi-Square dengan tingkat α=0,05. Simpulan dari penelitian ini adalah ada hubungan yang significant (p = 0,05) yaitu (0,000 < 0,05) antara paritas dengan kejadian plasenta previa. Kata kunci : Paritas, Plasenta Previa